New Brunswick: Development of a Web-based orientation program and enhancing senior nurses' mentoring skills - Auffrey, Marise; Cormier-Daigle, Monique; Gagnon-Ouellette, Anne (Nursing Leadership, 2012)
This project to help new nurse recruits integrate into the hospital work environment had two components: the development of a new web-based orientation tool in French for new recruits and mentor training for more experienced nurses. The aim of the first component was to redesign delivery of the nursing orientation program by assessing individual needs of new recruits and developing "just in time" information sessions with online access and e-learning modules. The second component aimed to develop a voluntary mentorship training program for senior nurses that offered training on the role and responsibility of mentors. A total of 30 orientation modules were created as resources that could be adapted to the needs of each nursing unit and accessed online. Sixty nurse recruits used the programs. A mentor training program was developed, and 28 nurses were trained as mentors. The mentorship literature and guides, produced in French, will be a valuable resource for francophone nurses across Canada.

Quel avenir pour les services sociaux et de santé des communautés anglophones du Québec ? - Carter, Jane (Déclin et enjeux des communautés de langue anglaise du Québec, 2012)
Chapitre 6

Défis associés à l’offre de services de santé et de services sociaux en français au Manitoba : perceptions des professionnels - de Moissac, Danielle; de Rocquigny, Janelle; Giasson, Florette; Tremblay, Cindy-Lynne; Aubin, Natalie; Charron, Marc; Allaire, Gratien (Reflets, 2012)
Les services de santé et les services sociaux en français ne sont accessibles qu’auprès d’un quart de la population francophone au Manitoba (de Moissac, 2011). Une pénurie de professionnels pouvant offrir des services en français est perçue comme un obstacle important pour les usagers qui recherchent ces services et pour les professionnels qui voudraient assurer un suivi en français pour leurs clients. Une hésitation à s’identifier comme francophone et un manque de connaissance des ressources disponibles en français contribuent-ils à cette perception de pénurie? Cet article traite des défis entourant l’offre de services de santé et de services sociaux en français au Manitoba et suggère des pistes de solutions. Mots-clés : disponibilité, accessibilité, minorité francophone, Manitoba, professionnels

Examining the geographic distribution of French-speaking physicians in Ontario - Gauthier Alain P.; Timony Patrick E.; Wenghofer, Elizabeth. F. (Canadian Family Physician, 2012)
Abstract: Objective: To determine how many physicians in Ontario express a proficiency in providing services in the French language, and to assess the geographic distribution of such physicians. Design: Population-based analysis of the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. Setting: Ontario. Participants: A total of 22688 GPs, FPs, and other specialists certified by the College of Family Physicians of Canada and the Royal College of Physicians and Surgeons of Canada who responded to the survey. Main outcome measures: First official language spoken and languages of competency to conduct practice. Results: The physician-to-patient ratio by first official language spoken is 1 physician per 138 Francophone patients in Ontario. There is 1 French-speaking GP or FP for every 297 Francophone patients, and most French-speaking physicians are located in southern Ontario (91.4%), at a ratio of 1 physician per 111 Francophone patients. The most promising French-speaking physician–to–Francophone patient ratios are found in southern Ontario (1:248 for GPs and FPs, and 1:202 for other specialists) and in urban Ontario (1:266 for GPs and FPs, and 1:209 for other specialists). Conclusion: Clearly, there is a promising number of physicians, relative to the amount of French-speaking residents in Ontario, who identified a competency in offering services in French. However, while the number of physicians who indicated a self-assessed competency to deliver health services in French is promising, it is the maldistribution of such services that is of concern. Thus, efforts must be made to attract French-speaking physicians to areas where there is the greatest demand, particularly in the northern part of the province. Résumé Objectif: Déterminer combien de médecins ontariens se disent compétents pour fournir, des services en français et vérifier la distribution géographique de ces médecins. Type d’étude: Analyse démographique du rapport de 2007 sur la réinscription annuelle à l’Ordre des médecins et chirurgiens de l’Ontario. Contexte: L’Ontario. Participants: Un total de 22 688 omnipraticiens (OP), MF et autres spécialistes diplômés du Collège des médecins de famille du Canada et du Collège royal des médecins et chirurgiens du Canada qui ont répondu à l’enquête. Principaux paramètres à l’étude: Première langue officielle parlée et langues de compétence pour la pratique. Résultats: En Ontario, le rapport médecin/patient dans le cas de la première langue officielle parlée est de 1 médecin pour 138 patients francophones. On compte un OP ou MF francophone pour 297 patients francophones et les médecins francophones sont localisés pour la plupart (91,4%) dans le sud de l’Ontario, où on observe 1 médecin pour 111 patients francophones. C’est dans le sud de l’Ontario que le rapport médecin francophone/patient francophone est le plus favorable (1/248 pour les OP et les MF, et 1/1202 pour les autres spécialistes) et dans les milieux urbains (1/266 pour les OP et les MF et 1/1209 pour les autres spécialistes). Conclusion: Il est certain qu’en Ontario, il y a un nombre encourageant de médecins qui, par rapport au nombre de résidents francophones, se sont dits compétents pour offrir des services en français. Malgré ce rapport favorable, c’est la mauvaise distribution de ces services qui est préoccupante. Il faudrait donc s’efforcer d’attirer des médecins francophones dans les régions où la demande est la plus forte, notamment dans le nord de la province.

Compétences linguistiques et qualité de services. Argumentaire pour des services de soins de santé en français de qualité - Gauthier, Hubert; Reid, Marc-André (Conseil communauté en santé en français du Manitoba, 2012)
Citation suggérée par les auteurs: GAUTHIER, Hubert et REID, Marc-André. Compétences linguistiques et qualité de services, Argumentaire pour des services de soins de santé en français de qualité, Rapport pour le compte du Conseil communauté en santé du Manitoba, déposé en mars 2012, 46 pages.

The language barrier : the overlooked challenge to equitable health care - Hussey, Nadia (South African Health Review, 2012)
This chapter examines the effects of language barriers on the access of patients and communities to quality health care. It also looks at communication challenges experienced by health professionals that provide this care. Using a case study of a rural hospital, the chapter highlights some of the challenges posed by the language barrier and explores current methods that English-speaking health professionals at this hospital use to overcome these difficulties. The case study findings indicate that the language barrier decreases work efficiency and the provision of holistic treatment. It makes communication time consuming, which increases frustration levels and decreases empathy, approachability and confidentiality. Current methods for overcoming problems include the use of untrained and ineffective interpreters - usually overworked nurses; linguistic codeswitching; and the use of a selection of key isiXhosa vocabulary. These methods have many drawbacks and are not suitable or sustainable. Recommendations for improving communication include the promotion of a culture of multilingualism, which includes language education as a part of professional development and the employment of trained interpreters. For multilingualism to occur, more research needs to be conducted, and the political will to address this problem must be demonstrated. Overcoming the language barrier needs to be prioritised and commitment must be made to implementing strategies that provide a multilingual patient base with a multilingual healthcare service.

Cadre de référence pour la formation à l’offre active des services de santé en français (n°978-0-9879240-1-8) - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

Reference framework: Training for active offer of French-language health services - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)